Megakaryocyte-Derived IL-8 Acts as a Paracrine Factor for Prostate Cancer Aggressiveness through CXCR2 Activation and Antagonistic AR Downregulation - Dahal, Sadan; Chaudhary, Prakash; Jung, Yi Sook; Kim, Jung Ae (Biomolecules and Therapeutics, 2023)
Prostate cancer is the fifth leading cause of cancer-related mortality in men, primarily because of treatment resistance, recurrence, and metastasis. In the present study, we investigated the role of paracrine interleukin-8 (IL-8) in the antagonistic expression of IL-8 and androgen receptor (AR), and the contribution of IL-8 to prostate cancer aggressiveness. In hormone-responsive LNCaP cells that do not express IL-8, recombinant IL-8 treatment significantly increased expressions of IL-8, CXC chemokine receptor 2 (CXCR2), matrix metalloproteinase (MMP)-2/9, Snail, and vimentin. IL-8 treatment significantly decreased AR and E-cadherin expression. IL-8-induced gene expression changes were suppressed by navarixin, a CXCR1/2 inhibitor, and gallein, a Gβγ inhibitor. In PC-3 androgen-refractory prostate cancer cells, IL-8 knockdown reduced expressions of CXCR2, MMP-2/9, Snail, and vimentin, and increased AR and E-cadherin expressions at the mRNA and protein levels. Co-culture with MEG-01 human megakaryocytic cells secreting high levels of IL-8 induced gene expression changes in both LNCaP and PC-3 cells, similar to those induced by IL-8 treatment. The altered gene expressions were accompanied by significant activation of transcription factor Snail in LNCaP and PC-3 cells. Treatment with the CXCR blocker navarixin inhibited the invasion of PC-3 cells but not LNCaP cells. However, invasion induced by MEG-01 was inhibited by navarixin in both LNCaP and PC-3 cells. The collective findings demonstrate that IL-8 enhances CXCR2 expression, which antagonistically regulates AR expression. More importantly, through changes in IL-8/CXCR2-regulated gene expression, IL-8 induces antiandrogen therapy resistance and epithelial-mesenchymal transition in prostate cancer.
Keywords: Androgen receptor (AR); CXCR2; Interleukin-8 (IL-8); Megakaryocyte; Microparticle; Prostate cancer